Non-convulsive status epilepticus with right arm apraxia: A case report - Barbara Ladisich; Ferdinand Otto; Lukas Machegger; Waltraud Kleindienst; Eugen Trinka; Giorgi Kuchukhidze (Epilepsy & Behavior Reports, 2020)
Non-convulsive SE (NCSE) is characterized by altered consciousness with or without slight motor manifestations or other phenomena such as aphasia, sensory, auditory, emotional, gustatory or other symptoms.A 69-year-old right-handed man developed the sudden onset of apraxia in his right arm. On admission, the patient was alert and well oriented. In his past medical history, an intracerebral hematoma (ICH) in the left temporo-parietal area was noted occurred five years before the current admission.An electroencephalography (EEG) showed rhythmic theta–delta activity with fluctuating frequency between 1.5 and 5 Hz in the left centro-parieto-temporal area, which promptly responded to the intravenous injection of 2 mg clonazepam and 1000 mg levetiracetam. Apraxia resolved completely and the EEG demonstrated intermittent non-rhythmic delta–theta slowing in the left temporo-parietal area. A cranial CT scan showed residual cystic encephalomalacia in the left temporo-parietal area due to the previous ICH. An MRI exhibited an old parenchymal defect in the left temporo-parietal area with a residual hemosiderin rim on the susceptibility weighted imaging (SWI) and no diffusion restriction on the diffusion weighted image (DWI).NCSE presented with right arm apraxia in our patient with a post-hemorrhagic residual parenchymal defect in the left temporo-parietal area.